Model-driven engineering of planning and optimisation algorithms for pervasive computing environments - Harrington, Anthony Christopher (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2010)
This thesis addresses the development of that class of pervasive computing applications that can be modelled as real-world planning and optimisation problems. Canonical examples of such applications are the control of transportation infrastructures, activities such as region-wide pollution monitoring and emergency-service management. The formal foundations of planning and optimisation problems are well established, however applying these techniques to pervasive computing applications is still a challenging task.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.